Investigation of Absorber Concentration Changes During Maneuvering Operation in VVER 1000 Reactor - R. S. Anisur; M. A. Uvakin (Глобальная ядерная безопасность)
Boron carbide, Dysprosium, Silver, etc have a lot of unique properties, high neutron absorption, chemical stability, high melting temperature, low density, and low price. These elements are widely using in the VVER power reactors. In this article was investigated the absorber cross-section, burring behavior and scram efficiency of these elements. If the control rod (CR) is made of only boron carbide chemical element and it will be used in the maneuvering mode then the power of a reactor will fall down drastically. But in this work main goal is that, which element will be required in the control rod, as a result, the reactor in the maneuvering mode work with different power without fall down power drastically. The result was calculated by the three programs GETERA, WIMS and SERPENT.